Analisis penggunaan bahasa pramuwisata dengan wisatawan pada kunjungan situs warisan budaya di kawasan heritage pasar badung denpasar - Ni Made Rinayanthi; I Gusti Ayu Eka Suwintari; Kadek Ayu Ekasani (Jurnal Kepariwisataan dan Hospitalitas, 2018)
Abstract Tour guides have an important role in promoting and guiding visitors by providing complete information about Pasar Badung. This study aims to (1) examine the use of tour guide language when guiding tourists to traditional market of Badung tourist area, (2) examine the grammatical structure of the language used by tour guides traditional market of Badung area, as well as (3) reviewing foreign tourists' understanding of the use of English by tour guides in Badung tourism area. Foreign tourists and tour guides are the sources of data in this study where their conversations are recorded and then reviewed based on appropriate linguistic theories. Data obtained qualitatively and analyzed using explorative and qualitative descriptive research methods. The results of the analysis indicate that the use of language by tour guides when guiding foreign tourists to the traditional market of Badung tourist area is dominated by the communication function, which provides complete information to tourists. The grammatical structure of the language used is analyzed morphomically and syntactically. There are several morphomic processes that are dominated by the derivation process and there is a syntax process that is dominated by the release of verbs. Although there is an inaccuracy in the use of English by tour guides, tourists can still grasp the meaning of tour guides’ utterance. Keywords: Language Use, Tour Guides, Cultural Heritage Sites